Pengaruh Variabel Makroekonomi Terhadap Index Harga Saham Syariah - Sri Herianingrum, Annisa.M.Zaimsyah, Alvira.A.Ayun, Khofidlotur Rofi’ah, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2020)
The purpose of this paper to investigate macroeconomic indicators affects sharia stock prices in Asia Muslim majority countries. This research used inflation, interest rates and exchange rate in Indonesia, Malaysia, Saudi Arabia and Bangladesh. This research use data panels and multiple linear regression analyses using Ordinary Least Square (OLS) method as parameter. The results shows inflation and exchange rates have no effect in sharia stock prices, while interest rates have negative effect. Implications for investors who want to invest in stocks to attention macroeconomic variables that affect movement of stock price, information that related macroeconomic conditions, information that predict fluctuation stock price. This study has limitations only focus in four countries in Asia and only use three most dominant macro variables. Future research can improved other macroeconomic variables such world oil prices and gross domestic income. Novelty of this research examines the Sharia stock market in Muslim majority countries in Asia.